AugNav: a location-based augmented reality system for outdoors navigation with smartphones - Rizzo, Agustín (2011)
Augmented Reality (AR) is one of the most revolutionary technologies of recent times. It makes possible to enhance the real world by contextualizing computer generated data overlaid on top of it. The AR paradigm opens the way for the development of innovative applications where the user perceives virtual and real objects as coexisting in the same space. With the advent of smartphones with ever increasing advanced features, AR has the opportunity to emerge as an interesting option to have wide ranging applications on these devices. In this paper, we present the design, implementation and testing of an AR client application targeting the Androidbased smartphones that will allow 2D and 3D efficient navigation in the real world enriched with virtual information through visual annotations contextually associated with the real places.